Ratio of Inter Canthal Distance to Mesiodistal Width of Upper Anterior Teeth of the Upper Jaw Between Batak and Minangkabau Tribe - Dewi Indah Sari; Sri Wahyuningsih Rais; Tri Suciati (Sriwijaya Journal of Dentistry, 2020)
Introduction. Indonesia is rich in diversity of ethnic groups, each of which has its own characteristics, including the Batak and Minangkabau tribes. One of these characteristics can be seen from the intercanthal distance and mesiodistal width of the six maxillary anterior teeth. This research was aimed to determine whether there is a difference in the ratio of the intercanthal distance to the mesiodistal width of the six maxillary anterior teeth between the Batak and Minangkabau tribes.Methods. This research is analytic observational with nonexperimental correlation design. The research subjects were 60 people with the subject inclusion criteria were aged> 17 years. The intercanthal distance was measured from the median angle of the right eye to the left in the study subjects. Mesiodistal width measurements of six maxillary anterior teeth were performed in the study model, measured from the mesial to the widest distal margin of each tooth. Both measurements were carried out using a digital caliper with three repetitions. Data were analyzed using Pearson correlation test and independent t-test.Results. The results showed a significant (p> 0.05) and strong relationship between the intercanthal distance and mesiodistal width of the maxillary anterior six teeth in both tribes. The results of the independent t-test showed that there was a significant difference between the two tribes (p <0.05) with the mean value of comparison in the Batak tribe 1:1.42 and the Minangkabau tribe 1: 1.45.Conclusion. There was a significant difference in the ratio of the intercanthal distance to the mesiodistal width of the six maxillary anterior teeth between the Batak and the Minangkabau.